Projeto e Especifica????o de um Mercado de Negocia????o de Espectro de Radiofrequ??ncia - Moreira , Jonas Lopes De (2023)
Radio-frequency spectrum sharing is crucial for wireless coexistence in rural and urban areas. Solutions should address the potential cyber threats and vulnerabilities that arise from the usage of IoT and open wireless communication technologies in the smart environments. This article introduces a new architecture for radio-frequency dynamic spectrum sharing called spectrum trading market (STM). STM can be applied to provide a trustable spectrum market for devices. Through temporary sales of licensed spectrum transmission rights, primary users are remunerated with IOTA cryptocurrency for renting their transmission rights to secondary users. The spectrum occupation verification is performed in this architecture by IoT devices equipped with sensing capability, which scan the medium and feed the STM database with spectrum occupancy information, remunerating the IoT owners for the spectrum sensing job. A proof of concept has been developed, and functional and performance tests have been performed. Experimental results show the STM applicability, yielding an average spectrum negotiation time around 12 seconds. Throughput tests show that the prototype architecture supports between 20 and 24 simultaneous requests per minute, providing a secure and efficient way to share radio-frequency spectrum resources, which is crucial to support smart environments while relying on integrated information and communications technologies. Keyords: Keyords: Dynamic spectrum sharing, dynamic spectrum access, IOTA, DLT, spectrum trade market, IoT, smart farming, cybersecurity